Peran Pendidikan Keluarga dalam Meningkatkan Kesehatan Mental Anak dan Remaja - Muqtakdir Nurfalaq Syarif; Ika Sastrawati; Poltjes Pattipeilohy; Andi Fitriani Djollong; Suryaningsih Suryaningsih (Journal on Education, 2024)
This study aims to understand the role of family education in supporting the mental health of children and adolescents through phenomenological methods. The subjects of the study were children, adolescents, and parents who had experiences related to family education and mental health. Data were collected through in-depth interviews with participants and analyzed using thematic analysis to find key themes such as emotional support, resilience, and communication patterns in the family. The results showed that emotional support from parents and open communication patterns have a positive impact on the mental health of children and adolescents, strengthening mental resilience, and improving their ability to manage emotions. Conversely, families with closed communication or lack of emotional support tend to increase the risk of mental disorders. The implications of this study suggest the importance of policies and intervention programs that support family education to increase parental awareness in creating a healthy environment for children's mental development.